PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UMKM DENGAN MENGGUNAKAN APLIKASI BERBASIS ANDROID DI PANCUR JAYA KABUPATEN BENGKALIS - Humairoh, Fitri; Yusralaini, Yusralaini; Nurulita, Suci; Aprina, Diana; Gustiani, Natasya Fahira (Komunitas Manajemen Kompetitif, 2024)
Abstract: Many Micro, Small and Medium Enterprises (MSMEs) actors still do not know or understand financial reporting. This service activity aims to improve the ability of MSME actors in preparing financial reports by providing training to MSME actors in Pancur Jaya Village, Bengkalis Regency, Rupat District. The method used is to use a training method for several MSMEs in Pancur Jaya Village on the preparation of android-based financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The result of this activity is that MSME players have an increased understanding in preparing financial reports using the android application.